2020
DOI: 10.3390/pharmaceutics12020156
|View full text |Cite
|
Sign up to set email alerts
|

Nano- and Microcarriers as Drug Delivery Systems for Usnic Acid: Review of Literature

Abstract: Usnic acid is one of the most investigated lichen secondary metabolites, with several proven biological properties with potential medical relevance. However, its unfavorable physico-chemical properties, as well as observed hepatotoxicity, have discouraged wide-range utilization of usnic acid as a promising therapeutic agent. In accordance with the growing research interest in the development of nanotechnology, especially in the arena of preparations based on natural sources of medicinal compounds, usnic acid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…There are limitations regarding the use of usnic acid in in vivo models of systemic infections, due to its low aqueous solubility and hepatotoxicity after systemic administration [ 40 ]. Therefore, investigations on the therapeutic use of usnic acid in vivo have been focused on the topical application of this compound, especially in the treatment of infected wounds [ 19 , 40 , 41 ]. The study conducted by Zhang et al [ 41 ] demonstrated through histopathological analyses that usnic acid had a healing effect in rats after its topical application.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are limitations regarding the use of usnic acid in in vivo models of systemic infections, due to its low aqueous solubility and hepatotoxicity after systemic administration [ 40 ]. Therefore, investigations on the therapeutic use of usnic acid in vivo have been focused on the topical application of this compound, especially in the treatment of infected wounds [ 19 , 40 , 41 ]. The study conducted by Zhang et al [ 41 ] demonstrated through histopathological analyses that usnic acid had a healing effect in rats after its topical application.…”
Section: Resultsmentioning
confidence: 99%
“…ere are limitations regarding the use of usnic acid in in vivo models of systemic infections, due to its low aqueous solubility and hepatotoxicity after systemic administration [40].…”
Section: Synergistic Antimicrobial Activity Of Polymyxin B Andmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that usnic acid inhibits inflammatory response and prooxidant damage in pulmonary tissue mice infected with pulmonary fibrosis as a therapeutic against pulmonary disease [16]. Studies on usnic acid encapsulated into lipid-based, polymeric and non-organic micro-and/or nanocarriers, as potential drug delivery systems are some efforts are in process to overcome its limitations [12,20]. Table 1 shows molecular structure, molecular weight and rotatable bonds of ligands used to dock with SARS CoV 2 protein and follows Lipinski's rule.…”
Section: Introductionmentioning
confidence: 99%